Review of Responsive Design Concept Based On Framework Materialize On The Website - Muhammad Rehan Anwar; Marviola Hardini; Mey Anggraeni (ADI Publisher, 2021)
Responsive web design is a website design that can adjust each size on each device. Based on the results of several respondents, 60% of respondents agreed that some websites were not able to adjust the display size on the web, 50% of respondents agreed that design affects the convenience factor, 58% of respondents agreed that the main content and functionality of websites that are difficult to access via mobile devices, 53% of respondents agreed that the appearance of a website that was not attractive had a bad effect on the comfort factor of the respondents, 50% of respondents also agreed that the website was not able to adjust the size on every mobile device. From the results of this review, it can be concluded that an unresponsive website greatly affects the inconvenience of users in accessing information through the website.